Prospect Analysis of the Collaboration of "Kalimasada" and "MBKM-A" Programs as Population Administration Service Innovations in the City of Surabaya: Analisis Prospek Kolaborasi Program “Kalimasada“ dan “MBKM-A“ Sebagai Inovasi Pelayanan Administrasi Kependudukan Di Kota Surabaya - Haryati, Eny (Procedia of Social Sciences and Humanities, 2022)
As a metropolitan city, Surabaya has a population of 2,971,300 people, consisting of 1,474,330 people (49.62%) men and 1,496,970 people (50.38%) women. This number causes the complexity of population administration service problems (Adminduk). The crucial problem is the discrepancy between de facto data and de jure data, caused by the high mobility of changes in population data due to births, deaths, in-migration and out-migration. The Adminduk Awareness Community Environmental Area Program (abbreviated: Kalimasada) is here to solve this problem. This study aims to: (1) determine the public's response to the Kalimasada program; (2) knowing the contribution of the Kalimasada program to data updating; (3) knowing the benefits received by universities in implementing the Independent Learning Campus Merdeka (MBKM). The method used in this research is: systematic review with a qualitative approach, namely Meta-Ethnography. Systematic review is used to identify, evaluate and interpret all research results that are relevant to the research objectives. The results of this study indicate that the collaboration between the Kalimasada and MBKM-A programs has very good prospects, which is corroborated by the data: (1) the public gave a positive response to this program (community, head of RT, village apparatus, sub-district head); (2) in each RT, there is an increase in updating population data; (3) Universities that are willing to collaborate are always increasing, and state that this program is very helpful in achieving the effectiveness of the MBKM program on their campus.